Relaxations and chain dynamics of sequential full interpenetrating polymer networks based on natural rubber and poly(methyl methacrylate). Issue 8 (11th November 2013) - John, Jacob; Klepac, Damir; Petković Didović, Mirna; Raju, K. V. S. N.; Pius, Anitha; Andreis, Mladen; Valić, Srećko; Thomas, Sabu
Abstract The relaxations of natural rubber (NR)/poly(methyl methacrylate) (PMMA) interpenetrating polymer networks (IPNs) were studied using dynamic mechanical analysis, electron spin resonance (ESR) and solid state NMR spectroscopy. Samples with a lower concentration of PMMA in IPNs (25 wt%) showed only one relaxation, which corresponds to NR with a slight shift to higher temperature. IPNs with 35 wt% of PMMA showed very broad transitions arising from β‐ and α‐relaxations in PMMA, with the β‐relaxation slightly shifted to lower temperature. These compositions also showed a higher modulus at all temperatures. Highly phase separated IPNs showed a complete drop of modulus at 423 K. Higher crosslinking in the NR phase increases the miscibility and decreases the temperature difference between transitions, while in PMMA it increases the phase separation and does not affect the β‐relaxation of the PMMA chains. The ESR results showed that PMMA chains located in the PMMA‐rich and NR‐rich domains have different motional characteristics. The strong interaction between PMMA and NR chains was also observed by carbonyl relaxation in solid state NMR spectra. It was found that medium level crosslinking is needed for better interpenetration between phases. © 2013 Society of Chemical Industry